Multidimensionality of Chemical Information in Male Greater Sac-Winged Bats (Saccopteryx bilineata) - Schneeberger, Karin; Voigt, Christian C.; Müller, Caroline; Caspers, Barbara A. (Frontiers in Ecology and Evolution, 2016)
The complexity of social signals is thought to depend on the complexity of social systems, but evidence from wild animals is scarce. Here, we investigated the chemical information provided by individual male greater sac-winged bats (Saccopteryx bilineata), a small, long-lived neotropical bat species with a harem-polygynous mating system. We analysed the chemical fingerprints of wing-sac liquids that are displayed by males in front of females. Specifically, we tested if fingerprints of 45 males included information about age (adult, juvenile), year of sampling, and distance between colonies. We confirmed age-specific differences in male-specific substances, but show furthermore that chemical fingerprints correlate with year of collection and distance between colonies. Thus, the wing-sac chemistry of male S. bilineata conveys a multitude of information, which can potentially be used by conspecifics, especially by females to assess the status of potential mates. Our study provides evidence for a multidimensionality of chemical information in a free-ranging mammal with high social complexity.